Targeting therapeutic T cells to the bone-marrow niche. (23rd February 2017) - Khan, Anjum Bashir; Carpenter, Benjamin; Santos e Sousa, Pedro; Velica, Pedro; Zech, Mathias; Bennett, Clare; Stauss, Hans; Morris, Emma; Chakraverty, Ronjon
Abstract: Background: Immunotherapy has demonstrated exciting curative potential in the treatment of lymphoid malignancies, but cancer cells have developed a variety of immune evasion mechanisms requiring targeted strategies. CXCR4 is a G-protein coupled receptor with crucial roles in homing, maintenance, and proliferation of a wide range of haematological cancers. We hypothesised that overexpression of CXCR4 in CD8 T cells (T-CXCR4) would improve homing to CXCL12-rich niches such as bone marrow, enhancing tumour killing. Methods: We transduced murine CD8 T cells with a retroviral vector encoding either the Cxcr4 gene coupled to a GFP marker or a separate inducible vector encoding Cxcr4 and GFP under control of the Tet-On system. For allogeneic bone-marrow transplants, irradiated BALB/c recipient mice received intravenous B6 donor bone marrow and subcutaneous A20 lymphoma cells on day 0, and B6 T-CXCR4 or control T cells on day 2. For in-vivo imaging of T-cell accumulation, anaesthetised mice received luciferase-positive transduced T cells and luciferin. Transgenic OT-1 CD8 T cells expressing T-cell receptors specific for the SIINFEKL peptide were used in vaccination experiments. Findings: In an allogeneic B-cell lymphoma model, T-CXCR4 were significantly better than control T cells at tumour control (p<0·0001, n=5 per group). In-vivo imaging did not demonstrate greater T-CXCR4 accumulation at the tumour site, suggesting superior per-cell function. In a vaccination model, OT-1 T-CXCR4 demonstrated substantially enhanced long-term persistence in bone marrow and spleen compared with control T cells (bone-marrow ratio 34 to 1, spleen 11 to 1; p<0·0001). T-CXCR4 express a distinctive CD62LHI CD122HI BCL2HI early memory phenotype post recall vaccination with increased effector cytokine production. This enhanced T-stem memory marker expression was not observed after in-vitro CXCL12 exposure and was specifically lost upon transfer to mice lacking interleukin 15 receptor α. Interpretation: Coupled with gene expression data, these results suggest that heightened antitumour efficacy is mediated by successful homing and competition for cell-extrinsic niche-related factors, in particular interleukin 15 presentation by CXCL12-abundant reticular cells. Preferential generation of enhanced early memory T cells with therapeutic superiority to effector-type cells currently used in investigational protocols has great relevance for the design of next-generation immunotherapies. Funding: Bloodwise.